Lightweight ontology architecture for QoS aware service discovery and semantic CoAP data management in heterogeneous IoT environment - Sukhavasi, Suman; Perumal, Thinagaran; Mustapha, Norwati; Yaakob, Razali (Tech Science Press, 2026)
The Internet of Things (IoT) ecosystem is inherently heterogeneous, comprising diverse devices that must interoperate seamlessly to enable federated message and data exchange. However, as the number of service requests grows, existing approaches suffer from increased discovery time and degraded Quality of Service (QoS). Moreover, the massive data generated by heterogeneous IoT devices often contain redundancy and noise, posing challenges to efficient data management. To address these issues, this paper proposes a lightweight ontology-based architecture that enhances service discovery and QoS-aware semantic data management. The architecture employs Modified-Ordered Points to Identify the Clustering Structure (M-OPTICS) to cluster and eliminate redundant IoT data. The clustered data are then modelled into a lightweight ontology, enabling semantic relationship inference and rule generation through an embedded inference engine. User requests, transmitted via the Constrained Application Protocol (CoAP), are semantically enriched and matched to QoS parameters using Dynamic Shannon Entropy optimized with the Salp Swarm Algorithm. Semantic matching is further refined using a bidirectional recurrent neural network (Bi-RNN), while a State–Action–Reward–State–Action (SARSA) reinforcement learning model dynamically defines and updates semantic rules to retrieve the most recent and relevant data across heterogeneous devices. Experimental results demonstrate that the proposed architecture outperforms existing methods in terms of response time, service delay, execution time, precision, recall, and F-score under varying CoAP request loads and communication overheads. The results confirm the effectiveness of the proposed lightweight ontology architecture for service discovery and data management in heterogeneous IoT environments.